EVALUASI IMPLEMENTASI PROGRAM PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT (PAMSIMAS) DI KECAMATAN KARANGRAYUNG KABUPATEN GROBOGAN - Andito, Bagus Danar; Subowo, Ari; Rostyaningsih, Dewi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
This research aims to analyze the changes that occur to the community Karangrayung Grobogan District with regard to access to clean water, sanitas, clean and healthy lifestyles as well as the strengthening of institutional capacity at the village level after the Pamsimas program, and to find out what aspects of the mempengaruhinyal. Locus were used in this study is in District 6 in the village of Karangrayung target Pamsimas, Ketro, mountain Rice, Jetis, Parakan, Sendangharjo and Temurejo. This research uses qualitative research methods are purely descriptive. The subjects in this study consists of 6 (six) main informant.Based on the results of the study showed that the program helped Pamsimas Karangrayung Subdistrict in community access to clean water, bowel habits and access to sanitation is also haphazard change for the better, but the improvement that occurred in some villages are still a bit. The aspects that influence the success of Pamsimas in district Karangrayung is a condition of social economic society, the clarity of the content policies, financial resources and the implementing actors support the program itself.Conclusions in this study is, the overall program pamsimas improve the quality of the target sub district Karangrayung village community, however an increase that occurred in several villages, still a little bit to it need to be ditingkatkanya some aspects that are considered to be less, so that this program can be optimized.